Etnofarmasi Tunas Bambu Kuning Sebagai Pengobatan Hepatitis di Wuluhan Jember - Vivin Hardiyanti Mutmainah; Abdul Aziz; Afiatus Sulvia Ningsih; Rafiatul Hasanah (Universitas Islam Negeri Maulana Malik Ibrahim Malang)
Observations on the efficacy of yellow bamboo in Wuluhan Village, Jember have been carried out since May-June 2021, this study aims to find information on local knowledge of the people of Wuluhan Village about the properties contained in yellow bamboo plants that can be used for traditional hepatitis treatment. This research uses two stages, namely the first to seek information by exploring the potential of the surrounding community by using participatory observation methods and open interviews that we carried out with several community leaders in Wuluhan Village, the second data collection process that we carried out was using a sample collection technique, namely the snowball technique. sampling and purposive sampling, if the data collection technique that we do is deemed insufficient, we ask for recommendations from sources to find other reliable sources of informants. Analysis of the data used is a literature study with the method of collecting data in the form of open interviews, based on the results of this study it is known that 88% of the people of Wuluhan Village use yellow bamboo shoots as a traditional treatment that can cure hepatitis.